Padres y educación (Journal of Parents and Teachers, 2014)
In this article, the author reflects on the importance and great benefit of parents' schools. To do so, he uses the example of the I Salón de Padres held in Santiago de Compostela, detailing its scope and contents.
Keywords: Parenting School; Education; Training; Families; Parenting School; Education; Training; Families